Persepsi Siswa Terhadap Profesionalitas Guru dalam Proses Pembelajaran Matematika - Dian Refdelina; Rhomiy Handican (Pendidikan Matematika FKIP Universitas Mataram, 2023)
This study aims to see how the professionalism of teachers in the learning process and students' perceptions of the professionalism of teachers in the learning process at school, because the professionalism of teachers guarantees the objectives of education. This research is a descriptive qualitative research where this research will analyze the opinions of 25 students from various schools sampled. The questionnaire used in this study is to obtain information related to students' perceptions of teacher professionalism in the learning process. Based on the results of the study, it is known that 96% of students agree that teachers have competence in teaching. In addition, 92.3% of students stated that teachers have a good understanding of the material presented. 100% of students also feel that teachers have excellent classroom management skills, 96.2% of students also feel that teachers have a friendly and open attitude towards student questions. Students also felt that the teacher gave positive feedback and was willing to help students' difficulties during learning very well (92.3%). Students also feel that teachers motivate students to learn effectively (96%) and students feel that teachers pay attention to students' needs well where 80% agree with the statement. Students also feel that teachers use various and interesting learning methods (92%), students also feel that teachers have the ability to manage and utilize technology well in learning (96.2%), students also feel that teachers have a strong commitment to helping students in learning (96%). Therefore, it can be concluded that teachers can be said to have good professionalism in learning.